2021
DOI: 10.1088/1361-648x/abfb90
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and physical properties of perovskite Sm1−x Sr x NiO3 (x = 0, 0.2) and infinite-layer Sm0.8Sr0.2NiO2 nickelates

Abstract: Recently, superconductivity at about 9–15 K was discovered in Nd1−x Sr x NiO2 (Nd-112, x ≈ 0.125–0.25) infinite-layer thin films, which has stimulated enormous interests in related rare-earth nickelates. Usually, the first step to synthesize this 112 phase is to fabricate the RNiO3 (R-113, R: rare-earth element) phase, however, it was reported that the 113 phase is very difficult to be synthesized successfully due to the formation of unusual Ni3+ oxidati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…Superconductivity is missing in the bulk infinite-layer nickelate [23,[44][45][46]. The puzzling limitation in the thickness of the infinite-layer thin film further warrants the importance of investigating the thickness dependency of the physical observables and electronic structure of the infinite-layer nickelate.…”
Section: Thickness Dependency and Role Of Strain And Interfacementioning
confidence: 99%
“…Superconductivity is missing in the bulk infinite-layer nickelate [23,[44][45][46]. The puzzling limitation in the thickness of the infinite-layer thin film further warrants the importance of investigating the thickness dependency of the physical observables and electronic structure of the infinite-layer nickelate.…”
Section: Thickness Dependency and Role Of Strain And Interfacementioning
confidence: 99%
“…Nevertheless, La 1−x Ca x NiO 2 and Pr 4 Ni 3 O 8 35 single crystals are metallic but not yet superconducting to date. In contrast, most reduced infinite-layer [32][33][34]77 and layered nickelate powders [19][20][21][22][78][79][80] are insulating-metallic (Pr, Nd) 4 Ni 3 O 8 pellets were, however, achieved with reductions using a sulfur getter to promote the removal of apical oxygens 81,82 . Thus metallicity in square-planar, or T 0 , nickelates may be exquisitely sensitive to the oxygen content like in T 0 cuprates 83 .…”
Section: Mbe Synthesis Of Ruddlesden-popper Nickelatesmentioning
confidence: 99%
“…Up to now, more bulk infinite-layer nickelate compounds with other rare earth elements or other dopants have been successfully synthesized. For example, in 2020, He et al [126] demonstrated the successful preparation of bulk polycrystalline infinite-layer Sm0.8Sr0.2NiO2. In 2021, Puphal et al [127] reported the synthesis of high-quality single-crystal infinite-layer La1-xCaxNiO2+.…”
Section: A Key Puzzlementioning
confidence: 99%